MODELING WATER DEMAND IN A GROWING PUBLIC UNIVERSITY IN NIGERIA (Nigerian Journal of Technology, 2020)
Nigerian university campuses are facing the twin problems of providing portable water of adequate quantity and quality and the sustainability of such supply. This paper examines the water demand status of a public University in Nigeria. Domestic, Public and Industrial water uses were considered while population forecasting was done using regression analysis for a 30 years design period (2018 – 2048). Results reveals possible population increase of 53.8 % by 2048 when the institution will clock 60 years. Water demand is also expected to rise sharply from 5,206 m3 day-1 (2018) to 10,959 m3 day-1 (2048); existing storage capacity cannot satisfy the current needs not to talk of the projected demand hence, a reservoir of about 11,000 m3 will be needed to service the university for the next 30 years; attracting more investments into the water supply system becomes imperative as the existing supplies from groundwater is unsustainable.  http://dx.doi.org/10.4314/njt.v39i4.35